Skeletal Muscle-Derived Stem/Progenitor Cells: A Potential Strategy for the Treatment of Acute Kidney Injury - Egle Pavyde; Romaldas Maciulaitis; Mykolas Mauricas; Gintaras Sudzius; Ernesta Ivanauskaite Didziokiene; Arvydas Laurinavicius; Neringa Sutkeviciene; Edgaras Stankevicius; Justinas Maciulaitis; Arvydas Usas (Stem Cells International)
Skeletal muscle-derived stem/progenitor cells (MDSPCs) have been thoroughly investigated and already used in preclinical studies. However, therapeutic potential of MDSPCs isolated using preplate isolation technique for acute kidney injury (AKI) has not been evaluated. We aimed to characterize rat MDSPCs, compare them with bone marrow mesenchymal stem cells (BM-MSCs), and evaluate the feasibility of MDSPCs therapy for gentamicin-induced AKI in rats. We have isolated and characterized rat MDSPCs and BM-MSCs. Characteristics of rat BM-MSCs and MDSPCs were assessed by population doubling time, flow cytometry, immunofluorescence staining, RT-PCR, and multipotent differentiation capacity. Gentamicin-induced AKI model in rat was used to examine MDSPCs therapeutic effect. Physiological and histological kidney parameters were determined. MDSPCs exhibited similar immunophenotype, stem cell gene expression, and multilineage differentiation capacities as BM-MSCs, but they demonstrated higher proliferation rate. Single intravenous MDSPCs injection accelerated functional and morphological kidney recovery, as reflected by significantly lower serum creatinine levels, renal injury score, higher urinary creatinine, and GFR levels. PKH-26-labeled MDSPCs were identified within renal cortex 1 and 2 weeks after cell administration, indicating MDSPCs capacity to migrate and populate renal tissue. In conclusion, MDSPCs are capable of mediating functional and histological kidney recovery and can be considered as potential strategy for AKI treatment.